A theories-in-use approach to building marketing theory - ZEITHAML, Valarie A. (Institutional Knowledge at Singapore Management University, 2020)
This article’s objective is to inspire and provide guidance on the development of marketing knowledge based on the theories-in-use (TIU) approach. The authors begin with a description of the TIU approach and compare it with other inductive and deductive research approaches. The benefits of engaging in TIU-based research are discussed, including the development of novel organic marketing theories and the opportunity to cocreate relevant marketing knowledge with practitioners. Next, they review criteria for selecting research questions that are particularly well-suited for examination with TIU-based research. This is followed by detailed suggestions for TIU research: focusing on developing new constructs, theoretical propositions (involving antecedents, moderators, and consequences), and arguments for justifying theoretical propositions. A discussion of TIU tradecraft skills, validity checks, and limitations follows. The authors close with a discussion of future theory-building opportunities using the TIU approach.